PENGARUH AMELIORAN ORGANIK TERHADAP SIFAT KIMIA TANAH DAN PERTUMBUHAN CABAI RAWIT (Capsicum annum L.) PADA TANAH BEKAS TAMBANG NIKEL - AINDO, SRI INTAN; NAMRIAH, NAMRIAH; DARWIS, DARWIS; LEOMO, SITTI; GINTING, SAHTA; RESMAN, RESMAN (Jurnal Agroteknos, 2022)
Nickel mining activities in Southeast Sulawesi have triggered the physical, chemical and biological degradation of soil. Therefore, the application of organic amendment was an alternative solution to restore the degraded soil. This research aimed to study the effect of ameliorant on soil chemical properties and the effect of ameliorant on yield of cayenne pepper on ex-nickel mining soil. This research was conducted on Field Experimentation Station. Faculty of Agriculture Halu Oleo University, from January to April 2021. This study was carried out using a Randomized Block Design (RBD), which consists of 4 treatments namely without ameliorant (B0), cow manure 60 (B1), biochar husk 60 (B2), cow manure + biochar husk (1:1) 60 (B3) with 4 replications. The results showed that overall ameliorant had an effect on increasing soil pH, Organic-C, available-P, available-K, and Cation Exchange Capacity. Soil pH increased from 4.32 to 6.1, C-organic increased from 0.78% to 1.89%, available-P increased from 3.87ppm to 16.87ppm, available-K increased from 10 mg 100g-1 to 40 mg 100g-1, Cation Exchange Capacity increased from 0.1 me 100g-1 to 75.11 me 100g-1, while total-N increased from 0.21% to 0,38%. Application of 60 (B1) of cow manure increased the plant height and the number of leaves by 29.65 cm and 51,25 respectively.